Skrining Fitokimia dan Uji Aktivitas Antioksidan Kulit Batang Matoa (Pometia pinnata) Dengan Metode 1,1-Diphenyl-2 picrylhidrazyl (DPPH) - Hamsidar Hasan; Nur Ain Thomas; Faramita Hiola; Anggun Sasmita Ibrahim; Fika Nuzul Ramadhani (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Pometia pinnata is a plant belonging to the Sapindaceae family that spread in the tropics, including Indonesia, which can be used as antioxidants. It is known to contain flavonoid compounds. Flavonoid is a substance that has antioxidants in capturing free radicals because it contains a hydroxyl group which is a reducer and can be beneficial for hydrogen donors to free radicals. This study aims to determine the chemical content and antioxidant activity of Pometia pinnata skin using 1,1-Diphenyl-2-Picrylhidrazyl (DPPH). Sample extraction was conducted using a multilevel extraction method with n-hexane, chloroform, ethyl acetate, and ethanol as solvents. The results showed that Pometia pinnata skin extract contains Alkaloids, Flavonoids, Saponins, Tannins, Steroids, and Terpenoids. While the value of antioxidant activity showed the IC50 value of n-hexane, chloroform, ethyl acetate, and ethanol extracts are 25, 5, 9, 4 µg/mL. The IC50 value indicates that the antioxidant activity is in an extremely strong category.